2022
DOI: 10.1186/s12967-022-03739-3
|View full text |Cite
|
Sign up to set email alerts
|

A circular network of purine metabolism as coregulators of dilated cardiomyopathy

Abstract: Background The crosstalk of purine biosynthesis and metabolism exists to balance the cell energy production, proliferation, survival and cytoplasmic environment stability, but disorganized mechanics of with respect to developing heart failure (HF) is currently unknown. Methods We conducted a multi-omics wide analysis, including microarray-based transcriptomes, and full spectrum metabolomics with respect to chronic HF. Based on expression profiling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Additionally, pathway analysis was performed to highlight the coverage of various metabolic pathways covered by our combined approach (Figure B). Among the detected pathways were Purine Metabolism and Glycerophospholipid Metabolism, key pathways involved in the metabolic processes of the human heart. It is important to note that metabolomic pathway analyses should be integrated with other “omic” analyses, such as proteomics and transcriptomics, to better understand alterations within the pathway. ,, To illustrate the enhanced coverage of the metabolome by using our approach, we selected a pathway known to be altered in many cardiac diseases (purine metabolism) , and highlighted the extraction method(s) in which each metabolite was found (Figure C). Remarkably, one of the metabolites was observed in only a single extraction – inosine diphosphate (IDP).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, pathway analysis was performed to highlight the coverage of various metabolic pathways covered by our combined approach (Figure B). Among the detected pathways were Purine Metabolism and Glycerophospholipid Metabolism, key pathways involved in the metabolic processes of the human heart. It is important to note that metabolomic pathway analyses should be integrated with other “omic” analyses, such as proteomics and transcriptomics, to better understand alterations within the pathway. ,, To illustrate the enhanced coverage of the metabolome by using our approach, we selected a pathway known to be altered in many cardiac diseases (purine metabolism) , and highlighted the extraction method(s) in which each metabolite was found (Figure C). Remarkably, one of the metabolites was observed in only a single extraction – inosine diphosphate (IDP).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, other than serving as building blocks for DNA, purine nucleotides such as ATP are crucial for providing cellular energy, intracellular signaling, and cofactors to promote cell survival and proliferation [49]. Several diseases have also been linked to purine metabolism [54]. In airways, purine is not only involved in the normal energy flow but can also serve as a VILI marker in bronchoalveolar lavage fluid [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that ASMCs responded to high stretch with marked changes in interactions between certain miRNAs and their target genes, including miR-370-5p-PDE4D, miR-543-PDE4D, miR-29b-3p-PDE7B, miR-370-5p-AK7, miR-148a-3p-AK4, miR-194-5p-ENPP1, and miR-146-5p-NME1, which may all impact the mitochondrial respiratory function. Among them, miR-370-5p-AK7 is more likely to be involved in ATP synthesis inside ASMCs during high stretch because AK7 is known to function as phosphotransferase in energy homeostasis, and as adenylate kinase to catalyze the production and breakdown of adenine nucleotide in a reversible transfer method [54]. It has also been shown that depletion of AK7 protein will lead to impaired mitochondrial respiratory function, especially the synthesis of ATP [61].…”
Section: Discussionmentioning
confidence: 99%
“…The produced xanthine is converted into uric acid by xanthine oxidase, which generates a significant amount of superoxide anions, causing cellular damage. Under low oxygen environments, the byproducts of the breakdown of adenosine and inosine serve as more efficient energy sources than extracellular glucose, thereby slowing the build-up of nicotinamide adenine dinucleotide (NADH) and offering a degree of protection to the cells ( Wang G. et al, 2022 ). In the present study, hypoxanthine and deoxyinosine levels were significantly increased in the HF rat model, indicating the presence of an energy imbalance in the HF rat model, which is consistent with research findings ( Berry and Hare, 2004 ).…”
Section: Discussionmentioning
confidence: 99%